Strategi Pemasaran Produk Gadai Syariah Dalam Upaya Menarik Minat Nasabah Pada Pegadaian Syariah Ups Simpang Mayang. - Nurul Fu'uda Firman; Rafidah Rafidah; Agusriadi Agusriadi (Komunitas Dosen Indonesia, 2025)
This research is based on the fact that the number of customers for gold pawn products is not as many as other products issued by the sharia pawnshop UPS Simpang Mayang. There were very few customers who used this product at the start of the interview. The problem in this research is what obstacles are faced by the sharia pawn shop UPS Simpang Mayang Jambi in marketing gold pawn products and what is the marketing strategy for gold pawn products in increasing the number of customers. This research is field research which is descriptive qualitative in nature with primary data sources and secondary data. In collecting research data using observation and documentation interview techniques. The marketing strategy at the Sharia pawnshop ups Simpang Mayang Jambi applies a marketing mix, namely product strategy, price strategy, place strategy and promotion strategy. The price strategy and location strategy are good because the prices given by Pegadaian have been determined by the head office, whereas for the location strategy before Pegadaian Syariah ups Simpang Wayang Jambi was established, a survey was carried out first but the product survey and promotional survey were not good because Pegadaian Syariah ups Simpang Mayang Jambi has not been optimal and introducing the product as well as the marketing strategy needs to improve promotional strategies to increase the number of customers, for example conducting outreach to the public